Role of bone morphogenetic protein signalling in bone destruction and niche maintenance in a mouse model of multiple myeloma. (25th February 2016) - Gooding, Sarah; Webb, Siobhan; Lwin, Seint; Olechnowitz, Sam; Snaith, Ann; Al-Hourani, Kinda; Armitage, Andrew; Pasricha, Sant-Rayn; Ramasamy, Karthik; Edwards, Claire; Drakesmith, Hal
Abstract: Background: The plasma cell malignancy multiple myeloma is usually incurable, partly because the bone marrow niche provides a protective microenvironment for quiescent tumour cells. We hypothesised that bone morphogenetic protein (BMP) signalling, a crucial regulator of cell differentiation in bone marrow, would be altered by multiple myeloma and that pharmacological interventions that manipulate BMP activity have potential to alter disease progression. Methods: In vitro, we used human and mouse cell lines and mouse primary stromal cells to test the interaction of BMP signalling with niche and tumour components. In vivo, we used the C57BL/KaLwRij mouse myeloma model to test the effect of BMP signalling disruption with a small molecule LDN-193189 (LDN) on disease progression (as measured by paraprotein and tumour cell number), bone lysis (micro-CT imaging of femoral metaphysis), and anaemia (haemoglobin and production of hepcidin). Findings: Tumour BMP signalling activity was increased 10 fold when myeloma cells were cultured with bone marrow stromal cells, but this effect was abrogated by BMP signalling inhibitor LDN. Expression of RANKL, a major mediator of myeloma-induced bone lysis, was reduced 1·6 fold by LDN in stromal cells from myeloma-bearing mice (p=0·03). Consistent with this, in vivo, LDN improved bone volume significantly in myeloma-bearing mice (total femoral bone to tissue volume ratio 36·2 vehicle group, 38·8 LDN group, n=10; p=0·015). LDN also altered the niche-preference (endosteal vs central marrow) of tumour cells to favour the endosteal niche, reported to house the quiescent stem fraction of a multiple myeloma clone (ratio of endosteal to central marrow myeloma cells 0·23 vehicle group, 0·37 LDN group, n=8; p=0·034). Serum hepcidin correlated with disease burden ( r 2 =0·55 p=0·03), which was partly reversed by LDN. Interpretation: Our findings show that BMP inhibition improves bone disease in multiple myeloma, possibly by reducing RANKL levels. RANKL inhibitors are effective in multiple myeloma bone disease, so there is potential for therapeutic benefit to BMP inhibition in this context. The additional benefit of hepcidin reduction could alleviate inflammatory anaemia associated with multiple myeloma. However, the LDN-induced alteration of niche preferences by tumour cells might imply changes to stem-cell quiescence, which is now being investigated. Funding: Wellcome Trust Research Training Fellowship.